A New Method for Separating Configurational and Constitutional Chiralities Using Diffuse Reflectance Circular Dichroism (DRCD). Issue 10 (October 2013) - Harada, Takunori; Nakano, Taku; Moriyama, Hiroshi; Tajima, Nobuo; Yokota, Haruo; Kawakami, Ryo; Mishima, Kenji
Solid-state chiral chemistry has attracted significant scientific interest because of its application in the chiral-selective production, chiral recognition, resolution, and detection of enantiomers of a chiral compound. Combining a novel diffuse reflectance circular dichroism (DRCD) technique with powder X-ray crystallographic analysis, we investigated the origin of chiral properties from the molecular and supramolecular chiralities and the possibility of separating independent CD signals from the superimposed CD signal resulting from different chiral origins.